Prolonged QT interval in bulimia nervosa - Buchanan, Ryan (BMJ Publishing Group, 2011)
A 39-year-old woman with an unremarkable history presented to the emergency department with three episodes of collapse. Each episode was witnessed by her son who described a loss of consciousness followed by rapid and complete recovery. The patient appeared well and examination was unremarkable. Her ECG showed a marked QTc prolongation of 642 ms (normal <470 ms) and low serum potassium at 1.8 mmol/l (3.5–5.3 mmol/l). The patient was moved to the coronary care unit and started on potassium replacement. On the ward a thorough history was taken and the patient confessed to being very conscious about his body shape and weight and admitted to episodes of binge eating and self induced vomiting. Her history suggested bulimia nervosa which is known to cause electrolyte disturbances and cardiac arrhythmia.1–4 Over the following 2 days the patient’s potassium increased and the QTc interval normalised; the patient was discharged with an outpatient referral for a psychiatric opinion.